Late-career unemployment and cognitive abilities - Diana Freise; Hendrik Schmitz; Matthias Westphal (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
We study the effect of unemployment on cognitive abilities among individuals aged between 50 and 65 in Europe. To this end, we exploit plant closures and use flexible event-study estimations together with an experimentally elicited measure of fluid intelligence, namely word recall. We find that, within a time period of around eight years after the event of unemployment, cognitive abilities only deteriorate marginally - the effects are insignificant both in statistical and economic terms. We do, however, find significant effects of late-career unemployment on the likelihood to leave the labor force, and short-term effects on mental health problems such as depression and sleep problems. – – Wir untersuchen die Auswirkungen der Arbeitslosigkeit auf die kognitiven Fähigkeiten von Personen im Alter zwischen 50 und 65 Jahren in Europa. Als Maß für kognitive Fähigkeiten nutzen wir einen experimentell ermittelten Wortgedächtnis-Score und verwenden Betriebsschließungen sowie flexible Event-Study-Methoden für die Identifikation des Effekts. Wir stellen fest, dass sich die kognitiven Fähigkeiten in einem Zeitraum von etwa acht Jahren nach dem Eintritt der Arbeitslosigkeit nur geringfügig verschlechtern - die Auswirkungen sind sowohl statistisch als auch ökonomisch insignifikant. Wir finden jedoch signifikante Auswirkungen von Arbeitslosigkeit im späteren Berufsleben auf die Wahrscheinlichkeit, aus dem Erwerbsleben auszuscheiden, und kurzfristige Auswirkungen auf die psychische Gesundheit in Form von Depressionen und Schlafproblemen.
Keywords: J14; J24; C21; I1; 330; Cognitive abilities; mental health; unemployment; event studies; plant closures